(3eHGgL GdacQ hefGgL GdYHQs - (3eMeO Hf EHQGgje Hf jMji Hf Ydj GdCfUGQj GdcJHj, LeGd GdOjf, GdeYQha H` GdhWhGW , J (B718 (3g` s
(3ChdgG (B:s
(3Ghd GdehLhO (B: (3aUd hjbGd Ef ai gPG GdfhY eG gh hMTi hjSei cHT GdLHd hNdbJg NdbI GdcHGFT GdGgdjI s
(3BNQgG (B:s
(3Je Gdaf GdKGdK ef efGgL GdacQ heHGgL GdYHQ ai GdWHGFY GdMjhGfjI jJdhg Gdaf GdQGHY ai GdbGOMGJ GdfHGJjI s
(3hgPG gh Gdaf GdKGdK ai GdWHGFY GdMjhGfjI GdbSe (B2s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B42s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3eJaQbGJs